(untitled) (International journal of artificial intelligence, 2026)
This paper assesses the impact of grid-connected photovoltaic (PV) panels on electric power quality in low-voltage distribution networks with growing inverter-based resources. The objective is to quantify variations in voltage magnitude, harmonic distortion, flicker severity, and power factor across realistic operating conditions and to identify the technical mechanisms that most frequently trigger noncompliance. The methodology integrates an analytical representation of inverter current injection, time-series simulations driven by measured irradiance and load profiles, and a compliance-oriented evaluation of power quality indicators used in distribution engineering. A comparative scenario design is applied across PV penetration levels, feeder impedances, and inverter control modes. The scientific novelty lies in an integrated assessment framework that explicitly couples inverter controls and network strength to a coherent set of quality metrics, enabling sensitivity ranking and targeted mitigation planning. The findings inform coordinated PV interconnection, voltage regulation, and harmonic management to preserve acceptable customer supply quality.